Conservation paleobiology on Minami-Daito Island, Okinawa, Japan: anthropogenic extinction of cave-dwelling bats on a tropical oceanic island - Kimura, Yuri; Fukui, Dai; Yoshiyuki, Mizuko; Higashi, Kazuaki (PeerJ, 2022)
Background With strong environmental and geographic filtration, vertebrates incapable of flying and swimming are often extirpated from island ecosystems. Minami-Daito Island is an oceanic island in Okinawa, Japan that harbors the Daito flying fox (Pteropus dasymallus daitoensis), a subspecies of the fruit bat and the only extant mammal endemic to the island. However, the skeleton of a cave-dwelling bat Rhinolophus sp. and fossil guano were briefly reported in a previous study. Methods Here, we present evidence for the anthropogenic extirpation of two species of cave-dwelling bats (Miniopterus sp. & Rhinolophus sp.) from Minami-Daito Island. Our goal is to reliably constrain the ages of the extirpated bat species by a multiproxy approach. Because skeletal materials did not preserve sufficient bone collagen for direct radiocarbon dating, we alternatively examined guano-like deposits based on SEM observation and Fourier-transform infrared spectroscopy (FTIR) along with stable carbon and nitrogen isotope analyses for possible indirect dating. We also examined stable carbon isotopes in bone apatite, assuming that an isotopic signal of C4 plants on the bat bones links to sugarcane plantation on the island based on the historical knowledge that early human settlers quickly replaced the island’s native C3 forests with sugarcane (C4 perennial grass) plantation from 1900 onward. Results Our cave survey documents the remains of Miniopterus sp. from the island for the first time. Based on the unique taphonomic conditions (unpermineralized bones, disarticulated skeletons closely scattered without sediment cover, various degrees of calcite crystal growth around bones) and a radiocarbon age of a humic sample, we suggest that the maximum age constraint of Miniopterus sp. and Rhinolophus sp. is 4,640 calBP. Based on a series of analyses, we conclude that the guano-like deposits are composed not of bat guano but mainly of humic substances; however, a hydroxyapatite crust associated with bat-lying stalagmites may be derived from bat feces. Stable carbon isotope analysis of bone apatite revealed C4 signals in various degrees, confirming that small populations of cave-dwelling bats persisted on Minami-Daito Island after 1900. Conclusions The results of this study indicate that these populations remained rather small and did not leave many generations and that the estimated ages can be bracketed from 4,640 calBP to the post-1900 (perhaps, until the 1950s). They likely faced a continuously high mortality risk due to severe anthropogenic stresses on the island, where most of the forests were turned into sugarcane plantations within a few decades in the early 20th century. A result of hearing surveys to local residents suggests the latest remnants most likely disappeared on the island concurrently with the introduction of chemical pesticides after World War II.
Keywords: Anthropogenic extinction; Extirpation; Chiroptera; Conservation paleobiology; Stable carbon isotopes; FTIR; Fossil guano; Insular mammals; Endemic species; Oceanic island